Naoxintong/PPARγ Signaling Inhibits Cardiac Hypertrophy via Activation of Autophagy. (15th February 2017) - Yuan, Shuping; Jin, Jianhua; Chen, Lu; Hou, Yongzhong; Wang, Hong
Abstract : As a traditional Chinese medicine, Naoxintong capsule (NXT) has been approved by China Food and Drug Administration (CFDA), which is used for cardiocerebrovascular disease treatment. Here we found that NXT extract significantly promoted H9c2 cardiomyocyte cell autophagy involved in increased autophagy-associated gene expression leading to inhibition of mTOR signaling. Moreover, NXT extract increased PPAR γ protein expression and transcription activity of H9c2 cell. Consistent with this, in PPAR γ gene silenced H9c2 cells, NXT had no effect on autophagy and mTOR signaling. Furthermore, NXT/PPAR γ -mediated H9c2 autophagy led to inhibition of cardiomyocyte cell hypertrophy. These findings suggest that the extract of NXT inhibited H9c2 cardiomyocyte cell hypertrophy via PPAR γ -mediated cell autophagy.